2014
DOI: 10.1159/000358791
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Diagnostics: Utilizing Oral Fluids to Determine Health Status

Abstract: Imagine a time where your health status could be available to you without the pain, discomfort and inconvenience of a physical examination. Distant vision of an inconceivable future or impending reality with potentially immeasurable impact? Recent advancements in the field of molecular diagnostics indicate this is not only possible, but closer than we think. Novel discoveries and substantial advancements have revealed that saliva may contain real-time information describing our overall physiological condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 56 publications
1
59
0
1
Order By: Relevance
“…We agree with Schafer CA et al, in that saliva offers a considerable leap forward in (Schafer et al, 2014), but as a first approach, it has to be clarified the best housekeeping genes for this corporal fluid to be used in qPCR.…”
Section: Resultssupporting
confidence: 89%
“…We agree with Schafer CA et al, in that saliva offers a considerable leap forward in (Schafer et al, 2014), but as a first approach, it has to be clarified the best housekeeping genes for this corporal fluid to be used in qPCR.…”
Section: Resultssupporting
confidence: 89%
“…However, for saliva microbiota, there’s only one report on a single sample from a healthy individual (Lazarevic et al 2012), yet what they focused is the bacterial profile, instead of functional feature. In this study, we choose unstimulated saliva as the origin of saliva samples, to avoid the potential that procedure of stimulated saliva sample collective may dilute or lead to quantity difference of the saliva microbiota (Schafer et al 2014; Yakob et al 2014; Belstrom et al 2016). Here we report the first metagenomic analysis of saliva using WGS sequencing to experimentally reconstruct the global genomic profile of saliva from two healthy (“H”) and two caries-active (DMFT ≧ 6) (“C”) adults.…”
Section: Discussionmentioning
confidence: 99%
“…Because each of the salivary glands is encapsulated by capillaries, each gland is allowed free exchange of blood-based molecules into the adjacent saliva-producing acinus cells. Previous research has suggested that circulating biomolecules that originate from a diseased process from the bloodstream may eventually be transported into the salivary glands, which will then consequently modify and change the composition of saliva [3,4,5]. Hence, it is of recent interest to locate saliva-based targets to evaluate an individual’s current state of health, as saliva is functionally equivalent to blood plasma or serum in diagnostic medicine.…”
Section: Properties Of Saliva As a Diagnostic Fluidmentioning
confidence: 99%
“…Currently, scientists have shown that these salivary constituents are effective indicators of many disorders. Multiple proteomic, transcriptomic, and microbiological markers have been identified for various pathologies: some prominent studies have been oral cancer, breast cancer, lung cancer, pancreatic cancer, and Sjögren’s syndrome [3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%